Erasmus Mundus Joint Master Degree Europäischer Master für Lexikographie/ European Master in Lexicography (EMLex). Sprawozdanie za rok 2017/2018 - Bielińska, Monika (Wortfolge. Szyk Słów, 2019)
Erasmus Mundus Joint Master Degree Europäischer Master für Lexikographie/European Master in Lexicography (EMLex)